Tin Extraction from Slags Used Hydrochloric Acid - Nonot Soewarno; Ali Altway; Susianto Susianto; Fadlilatul Taufany; Siti Nurkamidah (IPTEK The Journal of Engineering, 2014)
Slag is a mixture of mineral in tin sand or by product in the smelting process. By using separation process, tin can be separated from other minerals in slag. Extraction process with a solvent is usually used to separate tin from other minerals. Furthermore, solution that still contains many dissolved compounds is adsorbed by activated carbon and desorption back with NaOH solution. This study only focuses on the extraction process to obtain a stannate chloride solution with extraction temperature, solvent concentration, extraction time, and liquid/solid ratio as variables. Hydrochloric acid (HCl) has been used as solvent in this study. The concentration of tin in the extracts of each variable was analyzed to determine the percentage of recovery of tin and the optimum operating conditions in the recovery process of tin from waste slag. Experiment results show that the percentage of recovery increases with the increasing of extraction temperature and solvent concentration The highest recovery is 61.5% which is obtained when the extraction temperature is 80 ºC, concentration of HCl is 10 wt%, with a HCl solution and slag ratio is 7: 1 and extraction time is about 30 minutes.